Getting at the "what" and the "how" in symbiosis. Issue 1 (5th December 2016) - Newton, Irene L. G.
Summary: Symbioses are ubiquitous and have had a tremendous impact on the evolution of life on the planet. Indeed, endosymbiosis lead to the generation of the first eukaryotic cell and from that point onwards, eukaryotes have interacted with the other domains of life, sometimes forming persistent and necessary relationships that span generations. However, because the majority of hosts and symbionts are not easily manipulated, the intricate details of these symbioses, an understanding of the molecular underpinnings of these interactions, have not been elucidated. It is difficult to ask questions about the details of a host‐microbe symbiosis if either member cannot be cultured, genetically manipulated, or even housed in a laboratory. Several technological advances in recent years may address these difficulties, making it easier for researchers to ask mechanistic questions in symbiotic systems.